Influence of selenization atmosphere on the Cu2ZnSn(S, Se)4 thin films and its correlation to the performance of solar cells. (October 2017) - Chen, Guilin; Wang, Weihuang; Zhang, Biyun; Chen, Shuiyuan; Huang, Zhigao; Zhuang, Bin
Graphical abstract: Highlights: The summary of novel conclusions:. The effect of annealing atmosphere on the incorporation of Se into CZTS thin films was studied. Offer a controllable selenization route for CZTSSe thin films with different Se/S ratio. The influence of annealing atmosphere on the performance of devices was researched. Champion efficiency of 4.4% for oxides nanoparticles-derived CZTSSe solar cell was obtained. Abstract: Selenization is a key process to prepare Cu2 ZnSnSx Se4-x (CZTSSe) thin films from sulfide for high efficient solar cell. To explore the effect of annealing atmosphere on the substitution of S by Se in Cu2 ZnSnS4 (CZTS) thin films, different selenization atmosphere (Vacuum or Ar) are used. By examining the annealed sample, it is found that selenization under Ar atmosphere replaces S with Se more efficiently, resulting large grain and small band-gap. The reaction kinetics has been studied to explore such phenomena. It demonstrates that the substitution reaction is enhanced when the flowing Ar carries off S gas. Finally, the effect of annealing atmosphere on oxide-based CZTSSe devices has also been studied. The Vacuum selenized CZTSSe device shows a higher efficiency of 4.4%, due to the more appropriate band-gap. To the best of our knowledge, this is the best device performance in oxides nanoparticles-derived CZTSSe solar cell.